Get Answers to all your Questions

header-bg qa

Q : 1     Use a suitable identity to get each of the following. 

             (vii) (6x-7) (6x+7)

Answers (1)

best_answer

(6x -7) X (6x - 7) = (6x-7)^{2}
We use identity III for this which is 
                                                    (a - b)(a + b) =  a^{2} - b^{2}
In this a = 6x and b = 7
                                           (6x -7) X (6x - 7) = (6x)^{2} - (7)^{2} = 36x^{2} - 49    

Posted by

Gautam harsolia

View full answer